ESTIMATION OF DIFFUSE SOLAR RADIATION IN THE NORTH AND FAR NORTH OF CAMEROON - Lealea, Theophile; Tchinda, Rene (European Scientific Journal, ESJ, 2013)
The successful design and effective utilization of solar energy systems and devices for application in various facets of human endeavors, such as power and water supply for industrial, agricultural and domestic uses, largely depend on the availability of information on solar radiation characteristic of the location in which the system and devices should be situated. The diffuse radiation of four stations in North and Far North of Cameroon was estimated. A statistical analysis of monthly mean correlation was examined, using a 20 years recorded (1985-2005) of monthly mean diffuse solar radiation obtained at the four selected meteorological stations throughout the area of North and Far North of Cameroon. The accuracy of the candidate correlations were performed in terms of the three widely used statistical indicators, mean bias (MBE), root mean square errors (RMSE) and t-statistic (TS). The results indicated the correlations relating the diffuse fraction (kd ) with the clearness index (kt ) and the estimated diffuse monthly solar radiation.